American mother : the true story of a troubled family, motherhood, and the cyanide murders that shook the world - Olsen, Gregg (Grand Central Publishing, 2022)
An account of the crimes of Stella Nickell and her look-alike daughter describes how Nickell--with the possible help of her daughter--killed her husband in order to collect on an insurance policy.